Immunohistochemical study of the pancreatic endocrine cells of the Hystrix cristata (porcupine) - Timurkaan, Sema; Girgin, Aydin; Karan, Meryem (Ecole Nationale Veterinaire Toulouse, 2006)
The pancreatic endocrine cells of Hystrix cristata (porcupine) was investigated by Immunocytochemistry. Immunostaining methods have demonstrated immunoreactivity for insulin, glucagon and somatostatin. Spherical to spindle shaped endocrine cells were identified. Insulin immunoreactive cells were present in the central regions with high frequency, and few of these cells were also demonstrated in the mantle zones. Glucagon immunoreactive cells were mainly restricted to mantle zones but few of these cells were also demonstrated in the central zones. However, rare immunoreactive cells were found in the peripheral regions. Somatostatin immunoreactive cells were detected in the mantle zones and peripheral regions with moderate and rare frequencies, respectively. In addition some somatostatin immunoreactive cells were also demonstrated in the exocrine portions.
Keywords: immunohistochemistry; insulin; glucagon; somatostatin; pancreatic islets; endocrine cell; porcupine